Orthogonal polynomials : computation and approximation - Gautschi, Walter, 1927- (Numerical mathematics and scientific computation., 2004)
Orthogonal polynomials are a widely used class of mathematical functions that are helpful in the solution of many important technical problems. This book provides, for the first time, a systematic development of computational techniques, including a suite of computer programs in Matlab downloadable from the Internet, to generate orthogonal polynomials of a great variety.